Use of Temperature, Humidity, and Slaughter Condemnation Data to Predict Increases in Transport Losses in Three Classes of Swine and Resulting Foregone Revenue - Peterson, Erik; Remmenga, Marta; Hagerman, Amy D.; Akkina, Judy E. (Frontiers in Veterinary Science, 2017)
The United States Department of Agriculture (USDA) Animal and Plant Health Inspection Service (APHIS) conducts weekly surveillance of slaughter condemnation rates to provide early warning for emerging diseases and to monitor health trends in swine. Swine deaths in-transit are an animal welfare concern and represent lost revenue for the swine industry. This retrospective observational study used ambient temperature and humidity data from weather stations near US slaughter plants collected from 2010 to 2015 to predict the incidence and risk of death among swine in-transit and just prior to slaughter. The risk of death for market swine at a heat index (HI), which combines the effects of temperature and humidity, indicating moderately hot weather conditions between 85-92F was 1.37 times greater than that of the baseline temperature range of 54-79F. The risk of death for cull sows at an HI between 85-92F was 1.93 times greater than that of average temperatures ranging from 54-79F. Roaster swine (weigh < 220 lbs and often used for whole carcass roasting), however, had 0.80 times the risk when the HI was 85-92F compared to a baseline temperature of 54-79F. The risk of death for roaster swine at a minimum temperature between 40-50F was 1.21 times greater than that of average temperatures ranging from 54-79F. The risk of death for market swine at a minimum temperature range of 40-50F was 0.97 times that of average temperatures ranging from 54-79F. And for cull sows the risk of death at a minimum temperature range of 40-50F was 0.81 times less compared to average temperature ranging from 54-79F. Across the study period, cumulative foregone revenue, or revenue not realized due to swine condemnations, for all swine was $18.6 million and $4.3 million for cold temperatures and high HI ranges above the baseline, respectively. Marginal foregone revenue per hog in hotter months is higher due to seasonal peaks in swine prices. As a result of this study, the USDA-APHIS swine condemnation surveillance can incorporate weekly estimated HI values and ambient temperature data for slaughter establishments to provide additional information for analysts investigating signals (noteworthy increases above baseline) for ‘dead’ condemnations.